Luminescent indium phosphide nanocrystals formed from single-source precursors using fluoride-containing ionic liquids - Lee, Stephanie K. (Kansas State University, 2018)
Quantum dot (QD) or semiconductor nanocrystal research has propagated extensively over the past few years due to increasing interest in long lasting, renewable, and safe applications such as solar cells and LEDs. Quantum dots are utilized for their size dependent optical properties that are based on the quantum confinement effect. Cadmium-based materials dominated early quantum dot research, which led to honing of syntheses and expansion of our understanding of various mechanisms. Recently, however, current applications, such as solar cells, LEDs, and displays, for everyday consumers require less toxic materials. Indium phosphide (InP) is a possible substitute for cadmium-based materials as it is not intrinsically toxic and emits in the visible region from 450-700 nm. Despite the potential benefits to using indium phosphide, reproducible synthetic methods for obtaining stable QDs with narrow size distribution and high quantum yield still need to be refined. Using single-source precursors such as magic-sized clusters is a good starting place for addressing some of these challenges. InP magic-sized clusters are stable intermediates that are homogenously sized and readily isolable for later growth into InP nanocrystals. Our goal with the InP clusters was to determine their long-term stability and reproducibility as an InP precursor. The InP clusters are can be reproduced, have longer stability when stored as a solid, and we can produce luminescent nanocrystals. Producing highly luminescent InP nanocrystals without the use of HF or shell growth is a challenge. We used the 1-methyl-3-butylimidazolium tetrafluoroborate as our ionic liquid to determine the effect of various ratios of ionic liquid to an InP separate-source precursor on quantum yield. The 1:10 ratio of precursor to ionic liquid provided the highest quantum yield of 21%. These reactions were difficult to reproduce, because there were many factors that affected the synthesis, such as how soon the precursor is used, when the reactions are conducted in the microwave, and how the ionic liquid interacts with the microwave. When using 1-methyl-3-butylimidazolium hexafluorophosphate as our ionic liquid and the magic-sized cluster precursor, there was a spike in pressure in the microwave, and the reaction could not proceed due to the production of a gas. This ionic liquid is still capable of producing nanocrystals with an absorption feature. Understanding the mechanism of how these ionic liquids improve luminescence can lead to safer and more efficient syntheses. Ligand stripping and exchange is also a valuable tool for uncovering information about the surface chemistry. The Lewis acid, BF3, formed adducts with native surface ligands and produces polar, stable nanocrystals. Refining the precursor synthesis so that it's reproducible and producing luminescent nanocrystals were both time consuming processes. This work serves an entry into understanding the process of surface passivation and surface composition of the luminescent InP nanocrystals produced with magic-sized clusters and ionic liquids.
Keywords: Inorganic chemistry; Nonocrystals; Indium phosphide